Uncovering the geometry of the hot X-ray corona in the Seyfert galaxy NGC 4151 with IXPE - Gianolli V.E.; Kim D.E.; Bianchi S.; Agís-González B.; Madejski G.; Marin F.; Marinucci A.; Matt G.; Middei R.; Petrucci P.O.; Soffitta P.; Tagliacozzo D.; et al. (Oxford University Press, 2025)
We present an X-ray spectropolarimetric analysis of the bright Seyfert galaxy NGC 4151. The source has been observed with the Imaging X-ray Polarimetry Explorer (IXPE) for 700 ks, complemented with simultaneous XMM–Newton (50 ks) and NuSTAR (100 ks) pointings. A polarization degree Π = 4.9 ± 1.1 per cent and angle Ψ = 86° ± 7° east of north (68 per cent confidence level) are measured in the 2–8 keV energy range. The spectropolarimetric analysis shows that the polarization could be entirely due to reflection. Given the low reflection flux in the IXPE band, this requires, however, a reflection with a very large (>38 per cent) polarization degree. Assuming more reasonable values, a polarization degree of the hot corona ranging from ∼4 to ∼8 per cent is found. The observed polarization degree excludes a ‘spherical’ lamppost geometry for the corona, suggesting instead a slab-like geometry, possibly a wedge, as determined via Monte Carlo simulations. This is further confirmed by the X-ray polarization angle, which coincides with the direction of the extended radio emission in this source, supposed to match the disc axis. NGC 4151 is the first active galactic nucleus with an X-ray polarization measure for the corona, illustrating the capabilities of X-ray polarimetry and IXPE in unveiling its geometry.